(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the linguistic and cultural, as well as geographical features of zoomorphic phraseological units, with a specific focus on the representation of the image of the "camel" in phraseological expressions. The study compares the "camel"-based phraseological units in different languages, examining their semantic, stylistic, and geographical aspects. It reveals that the image of the "camel" is more actively used in the languages of peoples living in desert and semi-desert regions, which is closely linked to their way of life, natural environment, and economic activities. Furthermore, the article provides an academic explanation of how the mentality, cultural values, and worldview of these peoples are reflected in these phraseological units. This article is relevant for ethnolinguistics, phraseology, cultural studies, and geographical linguistics, contributing to a deeper understanding of the regional characteristics of language and culture.